Association between right heart dimensions and muscle performance and cardiorespiratory capacity in strength and endurance athletes. Issue 4 (18th March 2021) - Miranda, Douglas P.; Alves, Wilson Eduardo F. M.; Lopes, Heloísa H. M. C.; de Santana, Vinícius J.; Bocchi, Edimar A.; Salemi, Vera Maria C.
Abstract : Our purpose was to investigate the association between right heart dimensions and muscle performance and cardiorespiratory capacity in athletes. We selected 90 men with a mean age of 33.0 ± 8.0 years: strength group (SG), 30 bodybuilders; endurance group (EG), 30 endurance athletes; and control group (CG), 30 healthy non‐athletes. Comprehensive echocardiography and radionuclide angiography allowed the cardiac evaluation. VO2 peak was assessed by cardiopulmonary testing, muscle strength by the one‐repetition maximum test (1RM) and the relative strength (RS), and muscle endurance by the maximum repetitions test (MR) with 50% of 1RM. In SG was observed an association between right ventricle (RV) basal diameter and RS bench press ( R 2  = .188 β = 0.486 P  = .017) and between right atrium (RA) area and MR leg press ( R 2  = .257 β = 0.143 P  = .004). In EG was observed an association between RV basal diameter and VO2 peak ( R 2  = .299 β = 0.026 P  = .002) and between RA area and VO2 peak ( R 2  = .417 β = 0.092 P  ≤ .001). In conclusion, our data suggest that there is an association between right heart dimensions and muscle performance and cardiorespiratory capacity; moreover, muscle strength seems important for understanding cardiac adaptations to training.